Systematic Literature Review: How Important are Literacy and Numeracy for Students, and How to Improve it? - Rahmania, Ulya Ghifrani; Putri, Anggraita Febriana; Nurohman, Sabar; Salehudin, Achmad; Ria Rochmi Safitri (Indonesian Journal of Educational Research and Review, 2024)
The 21st century has changed how people communicate, work, and learn, which ultimately requires skills to face global situations. In addition, the COVID-19 pandemic has caused students in Indonesia to experience learning loss, resulting in gaps in students' learning abilities that are not at the standard. Literacy and numeracy abilities are decreasing, while these abilities are included in the 21st-century skills that must be mastered to master all aspects. This study aims to analyze the importance of literacy and numeracy. The systematic literature review (SLR) method will be used. The systematic literature review (SLR) method will be used. The two stages of SLR, namely the planning and conducting stages, refer to the analysis of how the data will be analyzed. SLR will play a role in summarizing and analyzing findings and various insights regarding issues related to literacy and numeracy. The systematic review will consider several research opinions discussing the importance of literacy and numeracy. The research results show that literacy and numeracy are partners like one unit in building a concept of understanding that can help learning and impact careers in the future. The findings relate to factors that can be used for literacy and numeracy: the environment, educators' attention, learning strategies, technology, and teaching literacy and numeracy across the curriculum.